2022
DOI: 10.1177/11206721221076952
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between anterior segment swept source-OCT and Scheimpflug imaging corneal aberration measurements in healthy eyes

Abstract: Purpose To assess agreement between corneal aberration measurements made through swept-source optical coherence tomography using a new anterior segment imaging device (Anterion) and a Scheimpflug imaging device (Pentacam HR) in healthy subjects. Methods Cross-sectional study. In 50 eyes of 50 healthy subjects, 14 aberration parameters (7 across the anterior corneal surface and 7 across the total surface) were measured in 4 mm and 6 mm optic zones using each device: oblique trefoil (Z3_-3), vertical coma (Z3_-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…No studies are currently evaluating the agreement between MS-39 measurements of corneal aberrations and those by other devices. Recent studies have reported agreement between the Anterion and Pentacam HR devices for corneal aberrations in healthy subjects [36,37]. Pe ´rez-Bartolome ´et al [36] indicated that vertical coma and RMS HOA values had good agreement, as the 95% LoAs ranged from -0.37 to 0.308 lm and from -0.27 to 0.305 lm, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…No studies are currently evaluating the agreement between MS-39 measurements of corneal aberrations and those by other devices. Recent studies have reported agreement between the Anterion and Pentacam HR devices for corneal aberrations in healthy subjects [36,37]. Pe ´rez-Bartolome ´et al [36] indicated that vertical coma and RMS HOA values had good agreement, as the 95% LoAs ranged from -0.37 to 0.308 lm and from -0.27 to 0.305 lm, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have reported agreement between the Anterion and Pentacam HR devices for corneal aberrations in healthy subjects [36,37]. Pe ´rez-Bartolome ´et al [36] indicated that vertical coma and RMS HOA values had good agreement, as the 95% LoAs ranged from -0.37 to 0.308 lm and from -0.27 to 0.305 lm, respectively. Gim et al [37] demonstrated that almost all HOAs had an acceptable agreement, except for the horizontal trefoil, and the 95% LoAs were -0.43 to 0.32 lm.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations